Pequi (Caryocar coriaceum Wittm., Caryocaraceae) Oil Production: A strong economically influenced tradition in the Araripe region, northeastern Brazil - Cavalcanti, Maria Clara Bezerra Tenório; Campos, Letícia Zenóbia de Oliveira; Sousa, Rosemary da Silva; Albuquerque, Ulysses Paulino (Ethnobotany Research and Applications, 2015)
The extraction of pequi (Caryocar coriaceum Wittm.) oil is a traditional activity that occurs between December and March. This extraction is performed by communities from the Araripe region, northeastern Brazil, and is very important to the local economy and culture. However, this practice has never been described in the literature. Thus, this photographic essay presents a description of this activity. The fruit are collected inside Araripe-Apodi National Forest (FLONA); oil production occurs in temporary settlements near FLONA, and oil marketing occurs on the highway and public markets in cities nearby this location. The Pequi Collectors’ Ranch Festival ends the process when typical pequi meals are made and sold and a Catholic mass is performed to give thanks for the harvest. In addition to being a significant cultural and economic practice, pequi oil production is an important part of local people’s lives. Therefore, we must encourage its socioecological sustainability.